A Human Long Non-coding RNA LncATV Promotes Virus Replication Through Restricting RIG-I–Mediated Innate Immunity - Fan, Jingjing; Cheng, Min; Chi, Xiaojing; Liu, Xiuying; Yang, Wei (Frontiers in Immunology, 2019)
Pattern recognition receptors sense pathogen components and initiate the host antiviral innate immune response, such as inducing interferons (IFNs). Long non-coding RNAs (lncRNAs) are emerging regulators of multiple biological processes. However, their role in antiviral response, especially through regulating the human innate immune, is largely unexplored. Here we characterized that lncATV, a human specific lncRNA, was up-regulated upon type I/III IFN stimulations and virus infection. LncATV was cytoplasmic localized and relatively high expressed in human monocytes, erythroleukemia cells and hepatoma cells. Notably, lncATV knockdown significantly inhibited the replication of multiple RNA viruses, such as hepatitis C virus, Zika virus, Newcastle disease virus, and Sendai virus. Mechanistically, RIG-I antiviral signaling and IFN effective pathway were enhanced when lncATV expression was knocked down but inhibited by overexpressed lncATV. RNA immunoprecipitation results demonstrated an association between LncATV and RIG-I. Collectively, our findings reveal the functional role of a novel human specific lncATV as a regulatory lncRNA restricting virus associated innate immune response.